Comparison of the editing patterns and editing efficiencies of TALEN and CRISPR-Cas9 when targeting the human CCR5 gene - Nerys-Junior,Arildo (2018)
Abstract The human C-C chemokine receptor type-5 (CCR5) is the major transmembrane co-receptor that mediates HIV-1 entry into target CD4+ cells. Gene therapy to knock-out the CCR5 gene has shown encouraging results in providing a functional cure for HIV-1 infection. In gene therapy strategies, the initial region of the CCR5 gene is a hotspot for producing functional gene knock-out. Such target gene editing can be done using programmable endonucleases such as transcription activator-like effector nucleases (TALEN) or clustered regularly interspaced short palindromic repeats (CRISPR-Cas9). These two gene editing approaches are the most modern and effective tools for precise gene modification. However, little is known of potential differences in the efficiencies of TALEN and CRISPR-Cas9 for editing the beginning of the CCR5 gene. To examine which of these two methods is best for gene therapy, we compared the patterns and amount of editing at the beginning of the CCR5 gene using TALEN and CRISPR-Cas9 followed by DNA sequencing. This comparison revealed that CRISPR-Cas9 mediated the sorting of cells that contained 4.8 times more gene editing than TALEN+ transfected cells.